Dampak implementasi pembelajaran dalam jaringan (daring) mengenai kualitas pembelajaran ipa di sekolah dasar pada masa pandemi covid-19 - Muhammad Isna Rosyada; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri (Didaktika Dwija Indria, 2021)
The Minister of Education and Culture of The Republic of Indonesia since March 24 2020 issued Circular No.4 of 2020 concerning the Implementation of Education Policies in an Emergency for the Spread of COVID-19, In this Circular Letter states that the learning process is carried out in their respective homes through online learning. The purpose of this study was to describe the impact of implementing online learning corncerning the quality of science learning during the COVID-19 pandemic. This research was conducted in class VI.I SDN Kleco 1 Surakarta. The research method used is descriptive qualitative with a case study approach. The data were collected by means of questionnaires and interviews from teachers and students as well as strengthened documentation. The results showed that through the implementation of online learning had an impact on not achieving on of the criteria in the indicator, namely the development of critical thinking in science learning. Teachers have not developed critical thinking in students, and students have not developed critical thinking. Based on this description it can be concluded that the quality of science learning in class VI.I SDN Kleco I Surakarta is quite good due to the impact of implementing online learning.